2017
DOI: 10.1097/hjh.0000000000001308
|View full text |Cite
|
Sign up to set email alerts
|

Increased high-risk coronary plaque burden is associated with arterial stiffness in patients with type 2 diabetes without clinical signs of coronary artery disease

Abstract: Coronary plaques with unfavorable characteristics are more prevalent in well controlled asymptomatic patients with type 2 diabetes compared with healthy controls and independently associated with arterial stiffness.Clinical trials registration number: NCT02001532.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 41 publications
1
17
0
5
Order By: Relevance
“…Proportional increases in PWV values with the severity of CAC score have also been reported . Furthermore, PWV was correlated with the presence and progression of stenosis or plaque development in the coronary arteries according to findings from CCTA in asymptomatic DM patients . Similarly, in asymptomatic individuals, PWV was identified as an independent prognostic factor for the presence of CAD diagnosed by CCTA .…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Proportional increases in PWV values with the severity of CAC score have also been reported . Furthermore, PWV was correlated with the presence and progression of stenosis or plaque development in the coronary arteries according to findings from CCTA in asymptomatic DM patients . Similarly, in asymptomatic individuals, PWV was identified as an independent prognostic factor for the presence of CAD diagnosed by CCTA .…”
Section: Discussionmentioning
confidence: 76%
“…33 Furthermore, PWV was correlated with the presence and progression of stenosis or plaque development in the coronary arteries according to findings from CCTA in asymptomatic DM patients. 14,34 Similarly, in asymptomatic individuals, PWV was identified as an independent prognostic factor for the presence of CAD diagnosed by CCTA. 15,35,36 In symptomatic patients, PWV levels were positively related to the presence and severity of CAD as assessed by invasive coronary angiography.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Patients with a high EATV have an elevated risk of coronary events and may need both lipid-lowering therapy and strict dietary manage-ment. 23) It is well known that EATV shows an association with the severity of coronary artery disease and with potentially unstable atherosclerotic plaque rather than stable plaque (fibrous plaque). 17,18,[20][21][22]24,25) Betteencourt, et al 14) and Gitsioudis, et al 15) previously found a positive correlation between EAT and the coronary plaque burden by using coronary CT.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial stiffening is a feature of physiological vascular aging that is accelerated in type 2 diabetes and a variety of pathological conditions associated with increased cardiovascular risk [6] . Coronary plaques are more prevalent in well controlled asymptomatic patients with type 2 diabetes compared with healthy controls and independently associated with arterial stiffness [7] . The prevention of arterial stiffness therefore plays an important role in the management of type 2 diabetes.…”
mentioning
confidence: 99%